Identification of dyes and matrices for dye doped polymer waveguide emitters covering the visible spectrum - L. F. Paz; M. Caño-García; M. A. Geday; J. M. Otón; X. Quintana (Scientific Reports, 2022)
Abstract Polymer based photonic devices offer the possibility cost effective roll-to-roll manufacture of photonic devices. The incorporation of luminescent dopants within a solid polymer waveguide allows for the generation of light within the device avoiding tedious mechanical light coupling. However, when a dopant is embedded in a solid matrix, depending on its concentration and the nature of materials involved, the emitted light may be quenched due to aggregation effects. In this work, thin films and ridge waveguides processed by UV-photolithography have been successfully obtained from a selection of standard photopolymerizable organic monomers, SU8, EpoCore and OrmoStamp doped with a selection of standard dyes like Rhodamine-B, Coumarin-540A and Pyrromethene-580. All structures were manufactured on glass substrates. An analysis of the solubility and optical properties including band gap energy, absorption coefficient ( $$α $$ α ) and fluorescence of the doped photoresists at different concentrations has been performed. Photoresists doped with Rhodamine-B shows a higher energy of indirect allowed band gap transition (2.04–2.09 eV) compared to previously reported pure Rhodamine-B thin films (1.95–1.98 eV). Fabrication protocols of dye doped photoresists covering the entire visible spectrum is established.